Supply chain management models : forward, reverse, uncertain, and intelligent foundations with case studies - Fazlollahtabar, Hamed (CRC Press, 2017)
"Supply Chain Management (SCM) is a wide field in which several specialties are included. In general, operations and production management players use SCM to organize the problems and analyze the solution approaches. Due to these points, a reference which can encompass a range of problems and their modelling approaches is required. This book will contain three general sections of forward, reverse, intelligent, and uncertain problems. While the book provides different problems in the three commonly used categories in SCM, it is very helpful for the readers to find out, or adapt their own application studies to the ones given in the book and employ the corresponding modeliing approach."- Resumé vydavatel